(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: Describe the clinical and subclinical characteristics of children with congenital hypothyroidism at the National Hospital of Pediatrics from January 2015 to January 2020; Subjects: We selected 52 pediatric patients diagnosed with congenital hypothyroidism and inpatient treatment at the National Hospital of Pediatrics from January 2015 to January 2020; Methods: Describe retrospective; Results: Through the study of 52 pediatric patients, we obtained the following results: most children with congenital hypothyroidism can be detected as early as 3 years, even in infancy. A suspected sign of constipation is accompanied by edema, prolonged jaundice, and delayed psychomotor development. Up to 86.5% had THS> 100 µU / ml, 78.8% had an FT3 of 1-2 pg / ml, 73.1% had an FT4 <0.4 ng / dl, 61.5% had anemia, 100% had delayed bone maturation on radiographs; Conclusions: Most children with congenital hypothyroidism can be detected as early as 3 years. A suspected sign of constipation is accompanied by edema, prolonged jaundice, and delayed psychomotor development. TSH > 100 µU/ml; FT3 of 1-2 pg/ml; FT4 <0.4 ng/dl; anemia; delayed bone maturation on radiographs.